Analisis Psikometri Burnout Assessment Tool (BAT) For Student Versi Bahasa Indonesia - Muh Haritsah Hizbullah; Afifah, Juliana Nur; Ulfah Sayidah Mutamimah; Ahmad Yasir Ibrahim; Alnaznabila Aghnii Hafnieva Imanda; Muhammad Arif Saefudin; Helli Ihsan (Journal of Research and Measurement in Psychology: JPPP, 2025)
This study aims to test the validity of the adaptation of the Burnout Assessment Tool (BAT) measuring instrument on university students in Indonesia. This scale consists of 6 dimensions and 33 items. The method used in this research is to use a validity test with content validity using expert judgment and also calculated CVI using Confirmatory Factor Analysis (CFA). with research subjects as many as 202 students of Universitas Pendidikan Indonesia. The results showed that BAT has an Alpha Cronbach reliability of 0.913 which is included in the high category. However, the results of confirmatory factor analysis showed a mismatch with fit index 0.001 (Chi-Square), 0.863 (CFI), 0.849 (NFI), and 0.068 (SRMR) so it was concluded that the adaptation of the Burnout Assessment Tool measuring instrument on students in Indonesia was invalid.